A Genome-Wide Association Study Identifies Novel Risk Loci for Sarcopenia in a Taiwanese Population - Wu SE (Dove Medical Press, 2021)
Shou-En Wu,1– 3 Wei Liang Chen2– 4 1Department of Dermatology, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan, Republic of China; 2Division of Family Medicine, Department of Family and Community Medicine, Tri-Service General Hospital; and School of Medicine, National Defense Medical Center, Taipei, Taiwan, Republic of China; 3Division of Geriatric Medicine, Department of Family and Community Medicine, Tri-Service General Hospital; and School of Medicine, National Defense Medical Center, Taipei, Taiwan, Republic of China; 4Department of Biochemistry, National Defense Medical Center, Taiwan, Republic of ChinaCorrespondence: Wei Liang ChenDivision of Geriatric Medicine, Department of Family Medicine, Tri-Service General Hospital, National Defense Medical Center, Number 325, Section 2, Chang-Gong Road, Nei-Hu District, Taipei, 114, Taiwan, Republic of ChinaTel +886-2-87923311 ext. 16567Fax +886-2-87927057Email weiliang0508@gmail.comPurpose: A genome-wide association study (GWAS) of sarcopenia unraveled the importance of genetic contribution to decline in muscle. The current study investigated sarcopenia-related single nucleotide polymorphisms (SNPs) in Asian older adults, and further constructed a genotype score that tests the combined effect of these SNPs on risk of sarcopenia.Patients and Methods: Ninety-six subjects aged 60 or above were recruited from the database of annual geriatric health examination at Tri-Service General Hospital during 2020. Eligible criteria included: 1) not having severe comorbidities; 2) agreed to join the Taiwan Precision Medicine Initiative project; and 3) having sufficient information of required sarcopenic measurements. Genotype–phenotype association analysis was performed to find SNPs that were significantly associated with each of three sarcopenic indices (low muscle mass, muscle strength, and physical performance). Subsequently, these SNPs comprised a sarcopenia-related genotype score that summed up the number of SNPs carrying unfavorable allele(s).Results: Twelve SNPs revealed suggestive genome-wide significance with the three sarcopenic indices, and eight of them revealed a relationship with more than one index. Low muscle strength was the item that had the most (eight) related SNPs. Among them, rs10282247 affects cholesterol binding and rs7022373 participates in cellular apoptosis. In addition, higher genotype score demonstrated higher risk of sarcopenia (≥ 4 points: OR=630.6; 2– 3 points: OR=408, p-value< 0.001).Conclusion: Several newly discovered SNPs suggest that genetic contribution plays a part in the pathogenesis of sarcopenia. Further studies are warranted to verify the underlying mechanisms. Moreover, a genotype score provides an estimate of the combined effect of genetic association with sarcopenia, which may modestly improve clinical risk classification.Keywords: sarcopenia, elderly, genome-wide association study, single nucleotide polymorphism